Revisiting E-Government Services in the Provincial Government of DKI Jakarta: A Case Study on the Management of Public Complaints - Riezka Novia Bewinda; Hadi Prabowo; Etin Indrayani; Gatiningsih Gatiningsih (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2024)
The government is increasingly using e-government to increase the efficiency of public services. This involves giving the community access to conveniently accessible electronic-based complaint communication methods. Thirteen electronic and non-electronic public complaint channels are available through the Provincial Government of the Special Region of Jakarta. The research objective is to delineate how the Jakarta Special Region Provincial Government has employed electronic-based channels for public complaint communication and to pinpoint the constituent elements involved in this approach. In-depth stakeholder interviews and Focus Group Discussions (FGDs) are two qualitative methodologies used in this research analysis to identify themes from the NVIVO coding data. The study's findings demonstrate that electronic-based public complaint communication channels improve accessibility, transparency, and response time for complaints. In addition, this circumstance facilitates the public's ability to express their goals and enables the government to pinpoint issues more precisely and swiftly. This demonstrates how crucial technology plays in fostering efficient and successful government communication.